Penyuluhan Demam Berdarah dan Pemanfaatan Pekarangan sebagai Strategi Pencegahan Berbasis Lingkungan - Kurniawan, Anugallakata Nea Sasgapata; Kharullah, Ilham; Sa'adah, Naili; Kholifah, Umi; Azizah, Rizky Annisa'; Mila, Zamilatul; Rahmawati, Putri; Shabrina, Nada Nasywa; Andriyani, Evita Ayu; Fahreza, Muhammad Nouval Raya; Munashiva, Nur Shifiya; Wangi, Nabila Mega; Agustina, Sofyya; Septian, Asya Ainu; Qoniah, Fadhilatul; Perdana, Fatkhi Zalfa (Yayasan Inspirasi El Burhani, 2025)
Introduction: Dengue Hemorrhagic Fever (DHF) continues to be a serious public health issue in Indonesia, including in Waru Village, Mranggen District, Demak Regency, where a rise in cases was recorded in 2024. Traditional prevention efforts such as the 3M campaign (draining, covering, and burying) and fogging have not been fully effective in reducing case numbers. This community engagement program aimed to enhance DHF prevention efforts by combining health education with the ecological use of home yards through the cultivation of mosquito-repellent plants. Method: The program was conducted by the KKN team from UIN Walisongo Semarang using a Participatory Action Research (PAR) approach, which involved active collaboration with PKK cadres and local residents. The implementation consisted of three stages: preparation, core activities (education and planting), and post-activity evaluation. Data were collected through observations, interviews, documentation, and reflective discussions with the community. Results: showed increased public awareness and participation in environmental hygiene practices. Residents expressed a better understanding of natural mosquito control methods and began planting and maintaining useful plants such as aloe vera (Aloe barbadensis), lemongrass (Cymbopogon citratus), and citrus (Citrus sinensis) in their yards. Interviews revealed positive behavioral changes and a collective commitment to sustaining these efforts. Conclusion: this program demonstrates that integrating health education with participatory environmental action can effectively strengthen community-based DHF prevention strategies and promote long-term behavioral change.